Game Changers of the C3 Value Chain: Gas, Coal, and Biotechnologies. Issue 1 (12th December 2012) - Ding, J.; Hua, W.
Abstract While ethylene crackers in Middle East and North America are shifting to ethane feedstocks and the volume of propylene production is becoming less, the market share of on‐purpose propylene production technologies keeps on increasing. In Northeast Asia, due to the shortage of naphtha and natural gas, methanol‐to‐olefin and methanol‐to‐propylene technologies attract much attention. In addition, biochemical technologies are impinging the propylene downstream. Using starch, sugar, or biomass as raw materials, important industrial chemicals such as acrylic acid, butanol, and 1, 3‐propanediol can be produced. Propylene glycol and epichlorohydrine can be manufactured using glycerine, the byproduct of biodiesel. All these factors are changing the traditional C3 value chain profoundly. The status of the game‐changing technologies related to the C3 value chain is presented. The relevant factors and the implications will be discussed.